Penerapan Konsep dan Teori Pembelajaran Jarak Jauh dalam Desain dan Pengembangan Materi Pendidikan yang Efektif - Fitria, Rias; Apriani, Nur Ida; Kharisbaya, Sofi; Hakim, Lukmanul; Hasani, Aceng (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the application of distance learning concepts and theories in the design and development of effective instructional materials. Using a literature review method, the research analyzes existing studies on distance education to identify the theoretical foundations and best practices in instructional material development. The results show that effective distance learning requires structured planning, the use of appropriate learning theories, and the integration of multimedia to support independent learning. Furthermore, the study highlights the importance of continuous evaluation and revision to maintain content quality and relevance. It is concluded that a pedagogically grounded approach in designing and developing digital learning materials is essential for successful distance education.